Revised Statutes of the State of Maine 683 (1840), tit. 12, ch. 159, § 5 - (:unkn) unknown (General Publisher, 1821)
Prohibited being armed with clubs or other weapons while in a group of twelve or more and "unlawfully, routously, riotously, or tumutluously assembled."
--
Keywords: CARRY - INTENT TO COMMIT CRIME